KURANGNYA ASUPAN ENERGI DAN LEMAK YANG BERHUBUNGAN DENGAN STATUS GIZI KURANG PADA BALITA USIA 25-60 BULAN - Ardian Nurdianto Firman; Trias Mahmudiono (The Indonesian Journal of Public Health, 2018)
The prevalence of underweight in 2010 to 2013 has increased percentage by 17.9% to 19.6%. Household food security and food intake were factors that can affect nutritional status of children.The aim of the study was to analize the relationship between status of household food security, energy and fat intake with nutrititional status of children. This was a cross sectional study with 40 samples selected using simple random sampling technique. Subject in this study was the fisherman family whose toddlers age 25-60 months. The data were collected by interview using questionaires, and were analyzed using linier regression and spearmen test. The result showed that 55% of households were facing food insecurity and 45% households were food insecure with severe hunger. Nutritional status of children (72,5%) were normal and (27,50%) wereunderweight. Energy intake has a significant relationship with nutritional status of children (p = 0,007) and fat (p=0,03).